The role of transcytosis in the blood-retina barrier: from pathophysiological functions to drug delivery - Zhang, Chun-Lin; Ma, Jing-Jie; Li, Xiang; Yan, Hai-Qing; Gui, Yong-Kun; Yan, Zhi-Xin; You, Ming-Feng; Zhang, Ping (Frontiers in Pharmacology, 2025)
The blood-retina barrier (BRB) serves as a critical interface that separates the retina from the circulatory system, playing an essential role in preserving the homeostasis of the microenvironment within the retina. Specialized tight junctions and limited vesicle trafficking restrict paracellular and transcellular transport, respectively, thereby maintaining BRB barrier properties. Additionally, transcytosis of macromolecules through retinal vascular endothelial cells constitutes a primary mechanism for transporting substances from the vascular compartment into the surrounding tissue. This review summarizes the fundamental aspects of transcytosis including its function in the healthy retina, the biochemical properties of transcytosis, and the methodologies used to study this process. Furthermore, we discuss the current understanding of transcytosis in the context of pathological BRB breakdown and present recent findings that highlight significant advances in drug delivery to the retina based on transcytosis.